Pharmaceutical services in the primary health care of the Brazilian Unified Health System: advances and challenges - Karen Sarmento Costa; Noêmia Urruth Leão Tavares; José Miguel do Nascimento Júnior; Sotero Serrate Mengue; Juliana Álvares; Augusto Afonso Guerra Junior; Francisco de Assis Acurcio; Orlando Mario Soeiro (Universidade de São Paulo, 2017)
ABSTRACT This study is a synthesis of the main results of the Pesquisa Nacional sobre Acesso, Utilização e Promoção do Uso Racional de Medicamentos (PNAUM - National Survey on Access, Use and Promotion of Rational Use of Medicines), Evaluation Component of the Basic Pharmaceutical Services. Based on the critical narrative of the elements of Brazil's pharmaceutical policies, we discuss aspects related to the structure of the pharmaceutical services, the medicines' sanitary state, human resources, access to medicines, rational use and management. Despite the advances that reflect the commitment of the group of actors involved, the results of the Survey indicate challenges, such as equitable access to medicines, the structuring of pharmaceutical services, the improvement of logistics and administration, and the implementation of actions directed to pharmaceutical care in the health units.